EVALUATION OF IMPACT OF ELEVATED TEMPERATURES ON YOUNG’S MODULUS OF GLT BEAMS - Lucie Kucíková; Michal Šejnoha; Tomáš Janda; Pavel Padevět; Guido Marseglia (Acta Polytechnica CTU Proceedings, 2021)
The influence of elevated temperatures on mechanical behavior of glued laminated timber beams is examined on the basis of tensile tests. Dog bone samples prepared from beams exposed to fire of variable duration were categorized with respect to the type and position of the failure crack, type and number of discontinuities such as knots, and the level of browning. The acquired experimental results suggest that the wood variability and the effect of growth discontinuities are probably more significant than the effect of elevated temperatures. To support this conclusion, further study is currently under way, exploring samples from the second series of the fire tests.